Obese Patients With a Binge Eating Disorder Have an Unfavorable Metabolic and Inflammatory Profile. Issue 52 (December 2015) - Succurro, Elena; Segura-Garcia, Cristina; Ruffo, Mariafrancesca; Caroleo, Mariarita; Rania, Marianna; Aloi, Matteo; De Fazio, Pasquale; Sesti, Giorgio; Arturi, Franco
Abstract : Abstract: To evaluate whether obese patients with a binge eating disorder (BED) have an altered metabolic and inflammatory profile related to their eating behaviors compared with non-BED obese. A total of 115 White obese patients consecutively recruited underwent biochemical, anthropometrical evaluation, and a 75-g oral glucose tolerance test. Patients answered the Binge Eating Scale and were interviewed by a psychiatrist. The patients were subsequently divided into 2 groups according to diagnosis: non-BED obese (n = 85) and BED obese (n = 30). Structural equation modeling analysis was performed to elucidate the relation between eating behaviors and metabolic and inflammatory profile. BED obese exhibited significantly higher percentages of altered eating behaviors, body mass index ( P < 0.001), waist circumference ( P < 0.01), fat mass ( P < 0.001), and a lower lean mass ( P < 0.001) when compared with non-BED obese. Binge eating disorder obese also had a worse metabolic and inflammatory profile, exhibiting significantly lower high-density lipoprotein cholesterol levels ( P < 0.05), and higher levels of glycated hemoglobin ( P < 0.01), uric acid ( P < 0.05), erythrocyte sedimentation rate ( P < 0.001), high-sensitive C-reactive protein ( P < 0.01), and white blood cell counts ( P < 0.01). Higher fasting insulin ( P < 0.01) and higher insulin resistance ( P < 0.01), assessed by homeostasis model assessment index and visceral adiposity index ( P < 0.001), were observed among BED obese. All differences remained significant after adjusting for body mass index. No significant differences in fasting plasma glucose or 2-hour postchallenge plasma glucose were found. Structural equation modeling analysis confirmed the relation between the altered eating behaviors of BED and the metabolic and inflammatory profile. Binge eating disorder obese exhibited an unfavorable metabolic and inflammatory profile, which is related to their characteristic eating habits.